Serum viral duplex-linear DNA proportion increases with the progression of liver disease in patients infected with HBV. Issue 3 (4th June 2015) - Zhao, Xing-Liang; Yang, Jian-Rong; Lin, Sheng-Zhang; Ma, Hui; Guo, Fang; Yang, Rui-Feng; Zhang, Heng-Hui; Han, Jin-Chao; Wei, Lai; Pan, Xiao-Ben
Abstract : Objective: HBV has two forms of genomic DNA, relaxed-circular DNA (rcDNA) and duplex-linear DNA (dlDNA). Compared to rcDNA, dlDNA has been demonstrated to integrate more frequently into host cellular chromosomes, which may have oncogenic consequences. However, the dlDNA proportion relative to total HBV DNA and its clinical significance in patients remain to be investigated. Design: Based on the structural difference between rcDNA and dlDNA, we developed a peptide nucleic acid (PNA)-mediated quantitative real-time PCR (qPCR) clamping assay to measure the proportions of dlDNA in total HBV DNA in sera obtained from patients with chronic hepatitis B (CHB), liver cirrhosis (LC) or LC-developed hepatocellular carcinoma (HCC). The factors that influence the proportion of dlDNA were also investigated. Results: The average dlDNA proportion was approximately 7% in the sera of chronic HBV-infected patients and was elevated in CHB patients with abnormal levels of alanine aminotransferase. The sera dlDNA proportions increased to approximately 14% and 20% in the patients with LC and HCC, respectively. Interferon-α treatment slightly increased the dlDNA proportion in the responders; and nucleotide analogue therapy spuriously elevated the proportion. Moreover, treatment of human hepatoma cells supporting HBV replication with inflammatory cytokines significantly altered the dlDNA proportion in vitro. Conclusions: Using a novel PNA-mediated qPCR clamping assay, we first showed that serum dlDNA proportions progressively increased during the development of HBV-related liver diseases. The dlDNA proportion can be regulated by inflammatory cytokines, suggesting an association among inflammation, increased production of HBV dlDNA and development of HCC.